Sickle cell disorders in females: Screening of sickle hemoglobinopathy be part of Antenatal and Intensive care? - Jitendra D. Lakhani; Varsha Shah; Dulari Gandhi; Niraj Pandit; Deep Mehta; Bakul Leuva; Jasmin Jasani; Pawan Toshiniwal; Sucheta Lakhani; A Muley; Hemal Dave; Paresh Golwala; et al. (Journal of Integrated Health Sciences)
Introduction: Women with sickle cell anemia may have complications especially during pregnancy. It may contribute to anemia in pregnancy. Methodology: As a part of Sumandeep Vidyapeeth's Sickle Project, this observational study of profile of 125 female patients was done. Observations: 125 female patients with sickle hemoglobinopathy who came either for antenatal checkup or for other health services in last 2 months were studied. 119 had sickle cell trait (SCT) while 6 (4.8%) had sickle cell disease (SCD). Majority of them were young, average age being 22.26 years. 14 (11+3, SCT and SCD) patients required indoor admissions. 3(SCT) patients were admitted in Critical Care Units, 7(6+1) in Obstetrics, 2(1+ 1) in medical and 2 (1+1) were admitted in pediatrics ward. Mean Hb of these 125 patients was 10.79 gm/dL, TC= 10702±3922/cu.mm, PCV of 32.70±7.98%, RBC count of 4.62±1.04 mil/uL, MCV=76.16±66.08fl, MCH=21.74±5.18pg, MCHC=28.35±8.74%, RDW-CV was 16.53±4.09. HPLC in percentage of A1a, A1b, A1c, LA1c and P3 were 0.96±0.72, 0.76±0.56, 4.90±0.81, 0.56±0.17 and 3.70±1.05 respectively. HBF=1.55±2.56, A0=57.34±11.69, A2=3.67±0.49 and S WINDOW was of 28.12±10.82.3. Out of 6 SCD patients,3 were admitted, 2 for severe Anemia and 1 for Crises. Mean Hb of SCD was 8.3±1.99 gm/dL, TC 15438±10562/cumm, PCV 27±5.75%, MCV 76.32±7.95fl, MCH=23.15±2.23pg, MCHC=30.37±1.75% RBC count of 3.60±1.04 Mil/uL, RDW-CV=21.73±6.99, HbS and HbF was 68.11±22.21% and 9.95 ± 6.3%. Conclusions: Female patients coming from tribal area may need screening for sickling during antenatal checkup. SCT patients may also have morbidity and may require hospital admission.